Penerapan Isometric Handgrip Exercise Untuk Menurunkan Tekanan Darah Penderita Hipertensi Derajat 1 - Dwi Budi Prastiani; Arif Rakhman; Siti Umaroh (Yayasan Literasi Sains Indonesia, 2023)
Hypertension is a disease that cannot be cured but should be controlled, therefore complications will not occurred. Hypertension can be treated by pharmacologically and non-pharmacological intervention. One of the non-pharmacological intervention of hypertension is isometric handgrip exercise which involves pressing the muscles on the blood vessels and when the pressure is released it can stretch the blood vessels and lower blood pressure. This study aims to determine the effect of isometric handgrip exercise on systolic and diastolic blood pressure among stage 1 hypertensive patients. This is a quantitative research using a quasy experimental design with one group pretest-posttest approach. The population of this study were all employees of Mitra Siaga Hospital in Tegal with stage 1 hypertension. The sampling technique that used was a total sampling technique with a total of 50 respondents. The results of statistical analysis using the Wilcoxon sign rank test showed p-value 0.000 (<0.05), which means that the application of isometric handgrip exercise can reduce blood pressure of stage 1 hypertensive patient. The results of this study are expected to be used as a reference in the management of hypertension, especially using isometric handgrip exercise as a non- pharmacological intervention for stage 1 hypertension which can be done independently.